Development Of The World of Moslem Program For The Youth Segment (Case Study on Muslim TV MNC Channels) - Viata, Sony; Budhi Waskito; Wawan Hernawan (International Journal of Education, Vocational and Social Science, 2025)
This research is titled "Development of the World of Moslem Program for the Youth Segment (A Case Study at Muslim TV MNC Channels)," motivated by the challenges of digital media in attracting the attention of young generations to religious content. This thesis aims to analyze youth perception of the "World of Moslem" program and formulate development strategies relevant to their needs and preferences, while simultaneously addressing the dynamics of digital transformation in the media industry. Utilizing a mixed-methods approach that combines quantitative surveys with qualitative interviews and observations, this study explores the stages of audience research, concept development, production, and program evaluation. Key findings indicate that although "World of Moslem" successfully maintained ratings in the 50-and-above age segment, the program was less effective in reaching youth audiences due to its conventional presentation format and lack of dynamic visual elements and interactivity favored by Generation Z. Therefore, this thesis recommends strategic innovations, including adjustments to the presentation style, visuals, communication, and themes to be more relatable for young viewers, as well as exploring collaborations with local vloggers and updating content based on viral trends. Technical and cultural challenges, along with competition from digital media, are also discussed as crucial factors for the future success of program development.